1993
DOI: 10.1007/bf00321199
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the trunk routes of a harvester ant to plant density

Abstract: Messor barbarus is a Mediterranean harvester ant that constructs physically defined trunk routes on the ground to connect nest entrances with foraging areas. Some responses of these trunk routes to plant density (and therefore resource abundance) were analyzed by testing the preferential allocation of different parts (trunk route ends, segments and branching points) in a patchy environment. Maps of grass density in four categories and Messor barbarus trunk routes were compiled for a Mediterranean pasture in Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 30 publications
4
33
0
2
Order By: Relevance
“…The presence of trunk trails was considered to be an indication of a potential foraging area, regardless of their trophic value. Of the three Messor species, only M. barbarus constructs conspicuous trunk trails for food searching, collection and transport (Cerdan, 1989;López et al, 1993b;Reyes-López and Fernández-Haeger, 2001), while those of M. bouvieri and M. hispanica are more seasonal and less visible. We therefore focused on M. barbarus in this part of the study.…”
Section: Sampling Designmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of trunk trails was considered to be an indication of a potential foraging area, regardless of their trophic value. Of the three Messor species, only M. barbarus constructs conspicuous trunk trails for food searching, collection and transport (Cerdan, 1989;López et al, 1993b;Reyes-López and Fernández-Haeger, 2001), while those of M. bouvieri and M. hispanica are more seasonal and less visible. We therefore focused on M. barbarus in this part of the study.…”
Section: Sampling Designmentioning
confidence: 99%
“…Finally, we defined the proportion of subplots crossed by trails (PST) for each plot and habitat type, and used these values as indicators of the extent of the foraging areas. The physical trunk trails of M. barbarus remain visible for several weeks even if they are not used (López et al, 1993b), eliminating the risk of bias due to the difference between the sampling period (August) and the months of maximum seed production in certain habitats (May -June in dry areas). 3) Seed predation risk.…”
Section: Sampling Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Many authors state that harvester ants are the main seed predators in Mediterranean grasslands (Azcárate & Peco 2003, Cerdá & Retana 1994, being the granivore Messor species the most important (López et al 1993a, Hensen 2002. Studies on floristic composition of Messor species diet show that they consume seeds from a wide variety of species, although it has been observed that their foraging strategy tends to reduce time costs by selecting preferably long propagules, which are more accessible and easily detectable (Reyes-López & Fernández-Haeger 2001, Hensen 2002.…”
Section: Introductionmentioning
confidence: 99%